TANGGUNG JAWAB PERDATA TERHADAP KREATOR KONTEN ATAS PENYEBARAN KOMIK ONLINE DI APLIKASI TIKTOK - Kartika Eka Rilani (Magister Hukum Universitas Semarang, 2023)
This research aims to discuss the civil liability for content creators and find out about legal protection for online comic creators in the TikTok application. Current developments make modified comics into digital forms that can be accessed in various applications or websites. This makes it easier for users to read comics online. The existence of online comics also makes it easier for copyright infringers to distribute them. The method used is to spread online comics by creating content on the TikTok application by content creators without permission from the online comic owner. As a result of the dissemination of other people's copyrighted works, it causes losses to online comic creators. Therefore, there is a need for protection for comic creators whose economic rights have been violated by the content creators. This study uses a normative juridical approach to legislation that is relevant to the issues discussed. The novelty of this research is based on online comics distributed through the TikTok application which have a commercial nature and are used for the benefit of copyright infringers. The results of this study are accountability in the form of compensation and submission of lawsuits against copyright infringers to the commercial court. As for the responsibility of the Tiktok application policy, such as deleting video content and blocking or closing the content creator's account. In addition to this, the form of legal protection for online comic creators is preventive and repressive protection.